Executive Power in Indonesia: Independent Institutions and the Unitary Executive Theory Perspective - Putri Mega Silvia Pa; Kamalia Firdausi; Rizkina Mewahni (Sabtida, 2026)
This article examines the presence of independent agencies that perform executive functions within Indonesia’s constitutional system as a normative critique of post-reform institutional design. The article discusses the concept of the Unitary Executive Theory, which developed in the United States as an adherent of a pure presidential system, the position of the President under the 1945 Constitution of the Republic of Indonesia, as well as the relevance and operationalization of this theory within the context of Indonesia’s constitutional system. The research employs a normative legal approach using four methodologies: the statutory approach, the conceptual approach, the comparative approach, and the historical approach. The conclusion of this article is that the 1945 Constitution of the Republic of Indonesia contains a sufficient constitutional basis for the application of the Weak Unitary Executive Theory; therefore, institutions performing executive functions should be under the President’s chain of command to ensure presidential accountability and consistency.